DAMPAK PERANAN EKONOMI KREATIF TERHADAP PENGEMBANGAN UMKM DI MASA TRANSISI (CAFE LOOKUP KOTA TASIKMALAYA) - Arnold Setia Damanik; Reza Sabila (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
After more than 2 years, Indonesia was hit by the Covid-19 pandemic, along with the decline in Covid-19 cases and a transition period, namely the easing of policies issued by the government aimed at starting the national economy. In this transition period, creative MSME actors must continue to struggle and take advantage of opportunities so that the business they run can survive and even develop. This study intends to find out how much impact and utilization it has on the creative economy, both creative economy products and policies issued by the government during the Covid-19 transition period. This research or research uses a qualitative approach. The data in this study used primary data and secondary data, secondary data was obtained through interviews, while secondary data to strengthen the first data used journal articles, and trusted websites, namely government sites. This study shows that there are various impacts of the creative economy on the sustainability of MSMEs in this transition period, both from policies and products that are the goals of MSME development in Indonesia.